ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒå¦é™¢ä¸æ–‡ä¸“ä¸š2016å±Šå¦ç”Ÿçš„æ±‰è¯å››å£°å‘éŸ³åè¯¯åˆ†æž - Kadarwati, Nancy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
There are 4 tones in Mandarin,There are first tone,second tone,third tone and fourth tone. The change in the pitch of tones used to differentiate meaning tones is one of the important features in Mandarin. The different tones will have different meaning too. Althought,the errorÂ  in pronouncing the tones after occurs but is easy to be realized. The writer has doneÂ  the research about the error in pronouncing the tones of the student of MandarinÂ  study program 2016 at Tanjungpura University. Based on the result ,The words that consists of one word and didinâ€™t use phonetic writing the highest errorÂ  in pronouncing the tones is 67,2% at second tones. On the otherÂ  hand,the words which used phonetic writing is 42,2%.The vocabulary which consist of two words and didnâ€™t use phonetic writing,the error in pronouncing.s percentage was the combination of thirds tones vocabulary and second tones is 87,5%. Whereas the words which used phonetic wrting is 78,1%. MoreoverÂ  ,the writer also did the research more intense about the cause of the error. There are mother tongue and foreign language. Based on those findings,the writer gave some suggestion on the issue.Key words:Â  PhonologyÂ Â  Â Â Â Â Â Â Â Â Â Â Â Â Â  Tones Â Â Â Â  Â Analysis of ErrorÂ